Disseminação da ciência via acesso aberto Science disseminaton using open access Book review - Blattmann, Ursula (Revista ACB, 2009)
Resenha do livro: CANESSA, Enrique; ZENNARO, Marco. Science Dissemination using Open Access: A compendium of selected literature on Open Access. ICTP - The Abdus Salam International Centre for Theoretical Physics 2008. 207p. ISBN 92-95003-40-3. Disponível em : http://sdu.ictp.it/openaccess/SciDissOpenAccess.pdf